A plastic approach to musical meaning: An analysis of The Barbarian by Emerson, Lake & Palmer - Gecevičiūtė , Agnė (Semiotika, 2016)
The aim of the present analysis is discussing a particular piece trying to answer rather impenetrable question of musical meaning. It is assented that in various contexts the same sound can create different meanings and that music can produce different meanings to separate people at different times. Thus music is considered as being more similar to plastic dimension of visual arts than submitting to a figurative reading. Therefore an aesthesic approach – the adaptation of plastic semiotics, which suggests reading the text in a more abstract way – might be also effective to music analysis. This is demonstrated in present analysis where trying to explore musical meaning in a particular piece, development of dynamics, rhythm, tempo, height and duration of sounds, timbres, accents, meter, (in)completeness, pulsation, curves of tension, etc. is discussed. The first piece of the debut album by one of progressive rock founding bands is analysed. It appears that in this object the main ideas of the band and of all progressive rock genre are expressed as well as roles of “high” and “mass” cultures are established.